2003
DOI: 10.1128/mcb.23.22.7965-7972.2003
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive and Lateral E-Cadherin Dimers Are Mediated by the Same Interface

Abstract: E-cadherin is a transmembrane protein that mediates Ca2؉ -dependent cell-cell adhesion. To study cadherincadherin interactions that may underlie the adhesive process, a recombinant E-cadherin lacking free sulfhydryl groups and its mutants with novel cysteines were expressed in epithelial A-431 cells. These cysteine mutants, designed according to various structural models of cadherin dimers, were constructed to reveal cadherin dimerization by the bifunctional sulfhydryl-specific cross-linker BM[PE0]3. Cross-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
86
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 34 publications
4
86
0
1
Order By: Relevance
“…The dissociation rate of strand-swapped dimers at cell-cell contacts in vivo may be slower than dissociation kinetics measured in vitro because in vivo dimers are likely reinforced by cis interactions (30,31). A similar Ca 2+ -independent stability has been described using cross-linking techniques for lateral dimers (32,33). Previous work examining cadherin dynamics (34) and the Ca 2+ dependence of cadherin interactions (35) demonstrated changes with a much longer latency (minutes or hours, rather than seconds) than we have observed here.…”
Section: Resultsmentioning
confidence: 86%
“…The dissociation rate of strand-swapped dimers at cell-cell contacts in vivo may be slower than dissociation kinetics measured in vitro because in vivo dimers are likely reinforced by cis interactions (30,31). A similar Ca 2+ -independent stability has been described using cross-linking techniques for lateral dimers (32,33). Previous work examining cadherin dynamics (34) and the Ca 2+ dependence of cadherin interactions (35) demonstrated changes with a much longer latency (minutes or hours, rather than seconds) than we have observed here.…”
Section: Resultsmentioning
confidence: 86%
“…All clones of human epidermoid carcinoma A-431 but Ec1M-C163A/V176C/ D155A-expressing clones were previously reported (Chitaev and Troyanovsky, 1998;Troyanovsky et al, 2003). New plasmids coding for this mutant were constructed using site-directed mutagenesis in the expression vector pRcCMV (Invitrogen, Carlsbad, CA).…”
Section: Cell Culture Dna Transfection and Plasmid Constructionmentioning
confidence: 99%
“…Cadherin sequences are numbered according to human E-cadherin (Bussemakers et al, 1993). Transfection, growth, immunofluorescence microscopy, and immunoprecipitation of the cells were done as described (Troyanovsky et al, 2003). In some experiments the actin filament inhibitors, cytochalasin D (Sigma, St. Louis, MO; final concentration 5 M) or latrunculin A (Molecular Probes, Eugene, OR; final concentration 0.2 M) were used.…”
Section: Cell Culture Dna Transfection and Plasmid Constructionmentioning
confidence: 99%
“…Although the cadherin cis interaction site was initially localized to the EC1 domains (10,24), it was later proposed that EC1 and EC2 domains of neighboring cadherin molecules are involved in these interactions (11,26). However, other studies using protein cross-linking and coimmunoprecipitation demonstrated that cis cadherin dimers were formed only in cells grown artificially at low calcium concentrations, and that cis and trans interactions shared the same adhesive interface (27)(28)(29). Although some electron tomography experiments have shown trans interactions involving both cadherin monomers and cis dimers (13), other cryoelectron tomographs suggest that cis dimerization is mandatory for trans adhesion (12).…”
mentioning
confidence: 99%